Case Study of Hybrid Micro Grid:- Small Hydro and Biomass Power Plant, in village of Punjab. - Manjeet Singh, Sundeep Singh, Pardeep Sidhu, Preetinder Singh,Ajay Vasishth, Bikramjit Singh (International Journal of Advanced Science and Technology, 2020)
Due to rapid industrialization and urbanization the difference between Demand and supply of electricity is increasing rapidly. Due to increasing energy demand, hiking the fossil fuel prices and increasing environmental problems, the trend of generating electrical energy using renewable source is setting up.Which can support electricity generation from conventional resources and ultimately replacing conventional resources which leads to reduce the environmental pollution. Several sources of renewableenergy are biomass, hydro, wind, solar, tidal, geothermal, and radiant energy. This paper has studied the use of combined operation of the small hydro and biomass power plant in the village of Punjab. The technique used are collection of data by surveying and interviewing the resource persons, Data calculation using MATLAB, 2015. This study gives the ideas of new micro hybrid grids to use renewable energy the results comes out as usinga Hybrid Power Plant of 10- 20MW in the village Tallewal,Punjab. The hybrid micro-grid using hydro and biomass power plant results in generation cost of Rs. 4.64.Payback period of biomass power plantis2.34 years and payback period of small hydro power plant is 4.06 years.